Fundamental Of Entrepreneurship (ENT300) : Patata Deliciosa / Dyg Atiqah Syahirah Awg Adam … [et al.] - Awg Adam, Dyg Atiqah Syahirah; Ibrahim, Nur Aina; Awg Kederi, Dyg Nursyifa Fazrin; Mohd Zollani, Farah Athirah; Adenan, Abdul Muzhaffar; Syamsul Amri, Mohammad Amir Hakimi (2019)
Patata Delicisiosa offers ready made fries and services for customers. Providing the ready made fries with variety of flavors that could meet the satisfaction of the customers. Our customers are identified or aimed to those who have lower income and who wants to consume the product with affordable price for example are students. Other than that, we also target customers with families, we also target busy customers such as workers and students as we provide delivery service..